Imaging in corporate environments technology and communication - Minoli, Daniel 1952- (McGraw-Hill series on computer communications, 1994)
Focusing on the specifics of imaging storage and transmission, this work examines standards and applications for work-stations, local networking, wide area/remote networking, storage and terminals, as well as future trends.